New Developments in Geopolitics: A Reassessment of Theories after 2023 - Georgios Tr Topalidis; Nick N. Kartalis; John R. Velentzas; Charalampia Gr Sidiropoulou (Social Sciences, 2024)
The scope of this article is to make a synthesis of the theory of geopolitics with new trends and characteristics of the new global environment. Traditional geopolitical theories are established on the basis of sovereign states. The starting point of many theories is for sovereign states to compete for world hegemony, or to gain an advantage in competition with their opponents. Geopolitical research also mostly starts from the interests of the country. However, as global environmental changes, transnational crimes, terrorism, information security, and other non-traditional security threats have become common threats to human society, their impact also crosses borders and has global characteristics, which also means solving geopolitical issues. Thinking needs to change from a national perspective to a global perspective. On the other hand, as the international community pays more and more attention to human rights, the challenge of human rights to sovereignty has become an unavoidable reality in current international politics. With the progress of the times, the protection and respect of civil rights has become the basic consensus of the international community. Nowadays, the issue of virtual rights such as carbon emission rights have also been included in the geopolitics theory, creating a strong shift of paradigm towards a renewed theory.